Human Resource Management Strategy in Improving Employee Performance (Study Case of GAPOKTAN Tambak Pocok, Tanjung Bumi, Bangkalan) - Ami, Peni Nevia Fitri; Maudina Alia; M Abbas Sastrodiputro; Iriani Ismail (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
One of the most important assets owned by a company is employee performance as measured by (HR) strategies. The aim of this research is to determine the importance of appropriate human resource management strategies so that they have an impact on improving employee performance. In this research we observed the implementation of human resource management at GAPOKTAN Tambak Pocok, Tanjung Bumi, Bangkalan based on employee performance by conducting interviews with employees and leaders. This research uses a qualitative method where the research sources are books, articles, journals and interviews so that research results are obtained which state that (HR) at GAPOKTAN Tambak Pocok, Tanjung Bumi, Bangkalan has a positive effect on employee performance